Das wort ozean ist ca. 20 quadratmillimeter gross. - Huet, Wilfried (Gent : HISK, 2019)
Casear, Sofia ; de Greeuw, Lisette ; Ferrei, Francesca ; Giolo, Eva ; Hansen, Johna ; Heilig, Megan-Leigh ; Hensel, Sina ; Heremans, Roel ; Klück, Mirthe ; Mevis, Hannah ; Požlep, Mark ; Sánchez Barroso, Bárbara ; Skvernyté, Gintauté ; Vaikla, Ingel
An island of multiple bridge (HISK laureates 2019 exhibition), HISK, Gent, November 21 til December 15 2019
boek